Clinical analysis of the retroperitoneal fibrosis with systemic lupus erythematosus - HU Hong-tao; GAO Yue; YAO Tao; ZENG Fang; CHEN Ling; SHUI Hua (Linchuang shenzangbing zazhi)
Objective To analyze the pathogenesis,clinical presentation,imaging findings,therapy and outcome of systemic lupus erythematosus(SLE) patient with retroperitoneal fibrosis(RPF),aiming to improve the understanding of clinicians on SLE in combination with RPF.Methods The details of one patient concurrently suffering from SLE combined with RPF in my department were collected and analyzed,and 7 cases of SLE combined with RPF reported abroad were reviewed to summarize the clinical characteristics.Results Including this case,a total of 8 SLE patients combined with RPF were selected for review.Six out of 8 were women with the age ranging from 17 to 54 years old[mean 30.5 years(30.5 ± 14.6)].Four patients were admitted into hospital for complaint of abdominal pain or back pain,3 for edema,and one for arthralgia.Laboratory abnormalities mainly included proteinuria,and hematuresis in all 8 cases.ANA was positive in 7 cases.Except one death of disseminated intravascular coagulation(DIC),the rest 7 cases achieved improvement with no relapse after discharge.Conclusions SLE in combination with RPF,a rare disease with the mechanism obscure,is considered an autoimmune disorder at present.CT and MRI are the two tests of choice in diagnosis and follow-up.A combination of corticosteroids and immunosuppressive drugs such as azathioprine is usually applied.Laparoscopic ureterolysis,or robotic ureterolysis,if available,is the technique of choice to relive obstruction.